(untitled) (Fiep Bulletin - online, 2013)
Sexuality is inevitable, relentless and irremovable part of human beings since birth, and in adolescence it begins to be experienced with more intensity. On this basis and in the Theory of Social Representation (TRS), proposed by Durkheim and produced by Serge Moscovici, this study aimed, among other things, identifying methodological practices best suited to psychosocial characteristics of adolescents, as well as their consciousness about the importance of the development of a healthy sexuality and a critical view on it. While respecting the ethical principles of Resolution No. 196/CNS/1996, the search was conducted with adolescents from the Program for Elimination of Child Labor (PETI) of Pium district, in the city of Parnamirim-RN, through meetings in which were worked a variety of topics related to sexuality issues, as well as other topics of interest of adolescents. After such meetings, we realized that many methods used in current practice are unsuitable for adolescents and, therefore, do not cause a change of attitude. With the passage of this project, the adolescents were more interested and safe when approached about sexuality, both with teachers and with parents.